2022
DOI: 10.1021/jacsau.2c00438
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of Cu(II)-Bound Amyloid-β Monomer Implicated in Inhibition of Peptide Self-Assembly in Alzheimer’s Disease

Abstract: Metal ions, such as copper and zinc ions, have been shown to strongly modulate the self-assembly of the amyloid-β (Aβ) peptide into insoluble fibrils, and elevated concentrations of metal ions have been found in amyloid plaques of Alzheimer's patients. Among the physiological transition metal ions, Cu(II) ions play an outstanding role since they can trigger production of neurotoxic reactive oxygen species. In contrast, structural insights into Cu(II) coordination of Aβ have been challenging due to the paramagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 88 publications
1
62
0
Order By: Relevance
“…Especially, the Cu 2 + and Zn 2 + have been demonstrated to dramatically regulate the selfassembly of the Aβ peptide into insoluble fibrils. [10] Generally, metal-bound species generate amorphous or low molecularweight oligomers which has highly polymorphic features and varied neurotoxicity. [11] According to the observation of high concentration of zinc in AD associated plaques, [12] zinc plays an important role in plaques formations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, the Cu 2 + and Zn 2 + have been demonstrated to dramatically regulate the selfassembly of the Aβ peptide into insoluble fibrils. [10] Generally, metal-bound species generate amorphous or low molecularweight oligomers which has highly polymorphic features and varied neurotoxicity. [11] According to the observation of high concentration of zinc in AD associated plaques, [12] zinc plays an important role in plaques formations.…”
Section: Introductionmentioning
confidence: 99%
“…[8d,17] The majority of theoretical studies indicate that H6, E11, H13, and H14 are the main binding sites of Zn 2 + at the N-terminus of Aβ. [17a,c,18] NMR spectroscopy [19] was in experiments to determine the binding structure of Zn 2 + to Aβ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Furthermore, our previous study found that Zn 2 + can have a strong effect on the structural and hydrophobic properties of Aβ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This energy landscape changes shape depending on the environment surrounding the amyloid molecules. It has been shown that cofactors, including the interaction of amyloid aggregates with lipid membranes, the effect of metal ions, , and interactions with other types of amyloid molecules, can lead to a variety of structural dynamics of the amyloid molecules. HS-AFM is an effective tool for visualizing the effects of cofactors.…”
mentioning
confidence: 99%
“…Indeed, since Aβ1−16 very well reproduces the coordination of Cu(II) and Cu(I) to Aβ1−42, Aβ1−40 and Aβ1−28, it is often used as a model for the longer peptide. [15,26,27] It is well known that, in the physical conditions of standard XAS experiments, which are typically performed at a temperature as low as 10 K, a progressive reduction of Cu(II) to Cu(I) is observed in the Cu-Aβ1−42 peptide complex in vitro.…”
mentioning
confidence: 99%